Disseminated histoplasmosis presenting as bilateral lower extremity paresis. (June 2020) - Simms, Andrew; Kobayashi, Takaaki; Endelman, Levi; Sekar, Poorani
Highlights: Disseminated histoplasmosis is a rare entity that occurs as a result of hematogenous spread of the organism within macrophages during acute infection. Risk factors for dissemination include HIV infection, being on TNF-α inhibitors, transplant recipients, and extremes of age. Organ systems affected in disseminated histoplasmosis can be numerous and include skin, bone marrow, central nervous system, gastrointestinal tract, and adrenal glands. The differential diagnosis for adrenal insufficiency should include histoplasmosis in endemic areas. Central nervous system histoplasmosis should be included in the differential diagnosis when a patient presents with meningitis, encephalitis, or isolated brain or spinal cord lesions in endemic areas. Abstract: Histoplasmosis is the most common endemic mycosis in the United States and is caused by the organism Histoplasma capsulatum . Infection is often asymptomatic or self-limited, but when symptomatic it usually presents in the form of pulmonary histoplasmosis. In its most severe form, H. capsulatum can spread to extrapulmonary sites causing disseminated infection. Here we present a peculiar case of central nervous system (CNS) histoplasmosis wherein multiple focal spinal cord lesions were the only manifestation of CNS infection, causing bilateral lower extremity paresis and loss of sensation. Although uncommon, CNS histoplasmosis should be included in the differential diagnosis when a patient presents with meningitis, encephalitis, or isolated brain or spinal cord lesions in endemic areas.